High temperature, low cycle fatigue characterization of P91 weld and heat affected zone material - Farragher, T.P.; Scully, S.; O'Dowd, N.P.; Hyde, Christopher J.; Leen, S.B. (American Society of Mechanical Engineers, 2014)
The high temperature low cycle fatigue behavior of P91 weld metal (WM) and weld joints (cross-weld) is presented. Strain-controlled tests have been carried out at 400 °C and 500 °C. The cyclic behavior of the weld material (WM) and cross-weld (CW) specimens are compared with previously published base material (BM) tests. The weld material is shown to give a significantly harder and stiffer stress–strain response than both the base material and the cross-weld material. The cross-weld tests exhibited a cyclic stress–strain response, which was similar to that of the base material. All specimen types exhibited cyclic softening but the degree of softening exhibited by the cross-weld specimens was lower than that of the base material and all-weld tests. Finite element models of the base metal, weld metal and cross-weld test specimens are developed and employed for identification of the cyclic viscoplasticity material parameters. Heat affected zone (HAZ) cracking was observed for the cross-weld tests.